2017
DOI: 10.5004/dwt.2017.20821
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and boron removal from spring and groundwater samples in boron mining regions of Turkey by electrocoagulation and ion-exchange consecutive processes

Abstract: a b s t r a c tBoron (B) and arsenic (As) are two important contaminants detected in the spring and groundwater around the Bigadiç borate mines in Turkey which have the largest colemanite and ulexite deposits in the world. In this study, electrocoagulation (EC) process was used for the removal of arsenic from waters since EC was capable of removing arsenic to trace levels. The removal efficiencies of arsenic from spring and groundwater samples containing different arsenic concentrations of 36-1021 µg/L at 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…3.2.1 Effect of reaction temperature. In order to investigate the effects of reaction temperature on the As(V) removal efficiency, adsorption experiments were conducted at six different temperatures (10,20,30,40, 50 and 60 C). In this experiment, 6 0.5 g portions of H/Fe were weighed out, and each was added to 1.0 L of arsenic-containing wastewater with an arsenic concentration of 1 mg L À1 .…”
Section: Effect Of the Main Environmental Factors On The Adsorption Omentioning
confidence: 99%
See 1 more Smart Citation
“…3.2.1 Effect of reaction temperature. In order to investigate the effects of reaction temperature on the As(V) removal efficiency, adsorption experiments were conducted at six different temperatures (10,20,30,40, 50 and 60 C). In this experiment, 6 0.5 g portions of H/Fe were weighed out, and each was added to 1.0 L of arsenic-containing wastewater with an arsenic concentration of 1 mg L À1 .…”
Section: Effect Of the Main Environmental Factors On The Adsorption Omentioning
confidence: 99%
“…7 Current treatment technologies for arsenic-containing water mainly include precipitation, adsorption, ion exchange, neutralization oxidation, ion otation, electro-occulation, extraction, membrane separation and biological method, among others. [8][9][10][11][12] Among them, due to its advantages of simplicity, low cost and environmental friendliness, adsorption is the most commonly used method to remove arsenic from wastewater. Various types of adsorbents have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocoagulation with iron plate electrodes were investigated, and Kobya et al (2017) found that the removal for arsenic could reach 97% to 99% in spring and groundwater samples. Addition of chemicals before the sedimentation exhibited different effects on particle settling.…”
Section: Coagulation/flocculationmentioning
confidence: 99%
“…Recently, As removal efficiency as high as >99% through the electrocoagulation (EC) process has been reported for many drinks of water and wastewaters ( Song et al., 2017 ; Kobya et al., 2017 ; Alcacio et al., 2014 ; Amrose et al., 2013 ; Molgora et al., 2013 ; Vasudevan et al., 2010 ; Parga et al., 2005 ). In the EC process, Electrochemical dissolution of sacrificial metal electrodes generates metallic hydroxide flocks within the water.…”
Section: Introductionmentioning
confidence: 99%